2015
DOI: 10.11604/pamj.2015.20.120.5501
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and predictors of hepatitis A infection in Nigerian children

Abstract: IntroductionHepatitis A infection is prevalent in developing countries where sanitation is still a public health issue. In Nigeria, there is no epidemiological data on children for this infection. A community based study was carried out to establish the seroprevalence and predictors of this infection in children.MethodsA community based cross sectional study was carried out in Akpabuyo local Government Area of Cross River State in southern Nigeria. Multi-staged sampling technique was used to recruit 406 childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 9 publications
2
7
0
Order By: Relevance
“…The subjects within the age bracket 21-40 years had the highest positive result of 32(2.2%) which is in accordance with the work done in University College Hospital, Ibadan, Nigeria with the highest prevalence on the 21-30 years age group 84(5.5%) [10] kobah et al reported a prevalence of 55.2% in a study of children from a Nigerian rural community of lower social economic background [10]. Hepatitis A virus infection is often asymptomatic in childhood and its morbidity and fatality increase by age.…”
Section: Journal Of Biomedical Sciences Issn 2254-609xsupporting
confidence: 87%
“…The subjects within the age bracket 21-40 years had the highest positive result of 32(2.2%) which is in accordance with the work done in University College Hospital, Ibadan, Nigeria with the highest prevalence on the 21-30 years age group 84(5.5%) [10] kobah et al reported a prevalence of 55.2% in a study of children from a Nigerian rural community of lower social economic background [10]. Hepatitis A virus infection is often asymptomatic in childhood and its morbidity and fatality increase by age.…”
Section: Journal Of Biomedical Sciences Issn 2254-609xsupporting
confidence: 87%
“…Moreover, one positive case was from a male and the other from a female. This is similar to the trend reported for HAV total antibodies among children in Akpabuyo LGA of Cross River State, Nigeria but with differences in prevalence rates probably due to differing number of study subjects, location, traditions and lifestyles [26,30].…”
Section: Resultssupporting
confidence: 86%
“…20 Long duration of stay in the community, probably reflecting longer exposure to risk factors and the virus, predicted the infection. 8 Neither Ikobah et al 8 in Nigeria, nor, Escobedo-Melendze et al 21 in Mexico were able to demonstrate significant association between type of waste disposal and water source, and HAV infection in children. This may be because these amenities were almost universally poor in the populations they studied.…”
Section: Drivers and Predictors Of Hav And Hev Transmission In Africamentioning
confidence: 91%
“…Ikobahet al 8 in southern Nigeria also demonstrated marked difference in prevalence rates between the socioeconomic groups with those in the low socioeconomic group having 6.5 times increased risk of infection compared to those in the high, with a 9% increased risk with every extra member of the household. 8 Crowded households is a major feature of the low socioeconomic group in Africa. 20 Long duration of stay in the community, probably reflecting longer exposure to risk factors and the virus, predicted the infection.…”
Section: Drivers and Predictors Of Hav And Hev Transmission In Africamentioning
confidence: 92%
See 1 more Smart Citation